2015
DOI: 10.1108/ijpsm-09-2013-0132
|View full text |Cite
|
Sign up to set email alerts
|

The compassionate organisation

Abstract: An additional written agreement between Emerald and BI Norwegian Business School states these rights to BI authors. 2The compassionate organisation: Contesting the rhetoric of goodwill in public sector value statements Abstract Purpose -This paper tests whether organisations in the public domain have embraced a corporate type of discourse, mirroring the private sector's preferred orientation towards expertise, or whether they maintain their traditional discourse of goodwill towards the publics they serve. At a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The student numbers are totals without conversion into the lower full-time equivalent figures. External political functions Fallis, 2008 Comparative topoi No subtypes discerned Karran, 2007 Change topoi No subtypes discerned Ramirez & Meyer, 2013…”
Section: Conclusion Discussion and Critical Postscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The student numbers are totals without conversion into the lower full-time equivalent figures. External political functions Fallis, 2008 Comparative topoi No subtypes discerned Karran, 2007 Change topoi No subtypes discerned Ramirez & Meyer, 2013…”
Section: Conclusion Discussion and Critical Postscriptmentioning
confidence: 99%
“…Newer social function topoi of the universities include, for instance, the worldwide diffusion of their 'third mission' (Laredo, 2007) and their 'corporate social responsibility' (Nejati et al, 2011). 'External political functions' topoi of the universities emphasize the enhancement of democracy by means of critical research (Fallis, 2008), and the active participation of scholars, teachers and students in public political deliberation (Hikins & Cherwitz, 2010).…”
Section: Tablementioning
confidence: 99%
“…This research is interesting with the aim of analyzing and explaining the dimensions of goodwill trust from the governance network perspective. The theory of goodwill trust is based on the theory of Jorgenson and Isaksson [6], who argue that goodwill trust has three main aspects: attention, obedience, and collaboration. As an independent and autonomous organization, as well as non-hierarchical in nature, the Housing, Settlement Areas, and Land Affairs Service as the leading sectors are in accordance with the characteristics of institutions in the governance network, and also based on the fact that the Housing, Settlement Areas.…”
Section: Klijn and Koppenjanmentioning
confidence: 99%
“…McCroskey's contribution then becomes a theory known as construct goodwill, which covers three dimensions: understanding, empathy, and responsiveness. Although thereby Jorgensen And Isakson [6] give an argument that the theory McCroskey about goodwill No in a manner direct support For direct we how to articulate will We For do something with Good. Study that tries to look for what underlying happening distance separates between construct attention, obedience, cooperation (collaboration) as means Which more real for para leader organization which tries in reach results which wanted.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the centrality of goodwill for persuasive attempts (e.g., Hunt and Wald 2020;McCroskey and Teven 1999), particularly exploring the context of science (Xu et al 2020). Some have also studied organizational efforts to create goodwill (Ihlen 2009;Jørgensen and Isaksson 2015), but primarily as related to consumers or the general public. For instance, a study of corporate social responsibility communication described the goodwill strategies of corporations under the moniker 'we care about you' (Ihlen 2009).…”
Section: Theorymentioning
confidence: 99%